(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
From the year 2000 in Argentina different projects began to develop, in order to open ‘Memory Spaces’ in places that had operated as Clandestine Detention Centers (CDC) during the last military dictatorship. In most of the opening experiences that took place across the country, it was possible to see new ways of management, as a result of the linkage between different agents who integrated ‘working and consensus sessions’, where representatives of government agencies and Human Rights organizations. An exponent of this process is the opening in 2014 of the ‘Espacio para la Memoria y Pro- moción de los Derechos Humanos ex CCD ESIM’, where the School of Non-commissioned Marines of the Marine Infantry had operated. The Punta Mogotes Lighthouse in the city of Mar del Plata still operates in this place, which led to the creation of the ‘Colectivo Faro de la Memoria’, composed by members of Human Rights, social and political organizations and representatives of public institutions and state agencies. The article will seek to develop the history of ‘recovery’ of the former CCD ESIM in Mar del Plata, showing its specific features and management.